(untitled) (Revista de Medicina Clinica, 2023)
Sjögren’s syndrome is a multisystem autoimmune disease that affects the salivary and tear glands, causing dry mouth and eye symptoms. In addition to classic symptoms, it can cause extraglandular ocular manifestations that can be life-threatening but may initially go unnoticed. A clinical case of anterior necrotizing scleritis is described in a patient with ocular symptoms of seven months’ duration and poor response to topical therapy, in which infectious and autoimmune diseases more related to this entity were ruled out, finally reaching the diagnosis of syndrome of anterior necrotizing scleritis. Sjögren. The patient responded favorably to immunomodulatory treatment with complete remission of symptoms. The association between scleritis and Sjögren’s syndrome is rare in the literature and its prognosis is unknown. This case highlights the importance of recognizing extraglandular ocular manifestations that may be the initial manifestation in this pathology.